2022
DOI: 10.3346/jkms.2022.37.e271
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Segmentation for Left Atrium With Convolution Neural Network Based on Active Learning in Late Gadolinium Enhancement Magnetic Resonance Imaging

Abstract: Background To propose fully automatic segmentation of left atrium using active learning with limited dataset in late gadolinium enhancement in cardiac magnetic resonance imaging (LGE-CMRI). Methods An active learning framework was developed to segment the left atrium in cardiac LGE-CMRI. Patients (n = 98) with atrial fibrillation from the Korea University Anam Hospital were enrolled. First, 20 cases were delineated for ground truths by two experts and used for training … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…One approach is transfer learning using networks that have been pre-trained on huge datasets in an unsupervised fashion and then fine-tuning for the specific task using a few (much fewer than if training from scratch) manually annotated examples ( 16 ). Another approach is ‘active learning’, in which the examples within the dataset that are most likely to contribute to network learning are selected for manual annotation ( 17 , 18 ). This can be combined with metrics of label uncertainty to identify the data that will yield the most performance-value from manual annotation ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…One approach is transfer learning using networks that have been pre-trained on huge datasets in an unsupervised fashion and then fine-tuning for the specific task using a few (much fewer than if training from scratch) manually annotated examples ( 16 ). Another approach is ‘active learning’, in which the examples within the dataset that are most likely to contribute to network learning are selected for manual annotation ( 17 , 18 ). This can be combined with metrics of label uncertainty to identify the data that will yield the most performance-value from manual annotation ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…They demonstrated a mean accuracy of 0.856 ± 0.033 and a mean DSC of 0.702 ± 0.071 for left atrium scar quantification. Even Cho et al used a 3D U-net architecture using a limited dataset of LGE CMR, demonstrating a DSC value of 0.90 [ 97 ].…”
Section: Ai In Cardiac Magnetic Resonancementioning
confidence: 99%
“…For instance, in the 2018 LA segmentation challenge (LASC) dataset [ 13 ], currently the largest open-source dataset for LA segmentation on late gadolinium-enhanced MRI (LGE-MRI) in patients with AF, the structure of interest was defined as the pixels within the LA endocardial surface, including the MV and the LAA, as well as the extent of the PV sleeves. In the datasets used in other selected publications, the definitions of the structure of interest vary, including solely the LA [ 14 , 15 ] or various combinations of the LA and its substructures [ 16 , 17 , 18 ] on contrast-enhanced CT (CECT) or LGE-MRI. In addition, Jin et al [ 19 ] proposed a model for the segmentation of the LAA on CECT, which is desirable for LAA occlusion procedures [ 20 ].…”
Section: Artificial Intelligence For Segmentationmentioning
confidence: 99%
“…Second, the framework utilized dilated residual learning to learn features from the sagittal and coronal views. Methods for direct 3D LA segmentation [ 14 , 26 , 27 ] have also been proposed. Borra et al [ 26 ] demonstrated that the 3D variant of U-net outperforms its 2D counterpart for LA segmentation.…”
Section: Artificial Intelligence For Segmentationmentioning
confidence: 99%